The Influence Of Online Learning On Fiqh Learning Motivation In Students At MI DDI Tani Aman Loa Janan Ilir Samarinda - Selvia Septianingsih (Mauriduna : Journal of Islamic Studies, 2025)
The COVID-19 pandemic has drastically changed the learning system, including at the madrasah ibtidaiyah (MI) level. The fiqh learning that was originally carried out face-to-face was transferred to online through WhatsApp media. This study aims to determine the effect of online learning on students' fiqh learning motivation at MI DDI Tani Aman Loa Janan Ilir Samarinda. The background of this study is the change in learning patterns due to the Covid-19 pandemic which requires students to learn online, while learning motivation is an important factor in learning success. The method used is quantitative with product moment correlation technique and t test. The research sample amounted to 78 students selected through total sampling technique. The instrument in the form of a questionnaire was distributed through Google Form, and the data was analyzed using SPSS version 22. The results showed that there was a positive and significant relationship between online learning and fiqh learning motivation with a correlation value of r = 0.622 and a value of t_hitung = 8.830> t_table = 1.664. The contribution of online learning to learning motivation is 38.7%. This result is reinforced by interview data with teachers which shows that effective online teaching strategies, such as the use of videos, assignments, and verbal motivation, support students' enthusiasm for learning. Thus, it can be concluded that online learning has a positive influence on students' fiqh learning motivation. This study offers a new perspective by focusing on fiqh learning at the elementary madrasah level using WhatsApp as the primary medium. The findings imply the need for teachers to optimize simple digital tools to maintain student motivation in religious education contexts.